2003
DOI: 10.1097/00002030-200309050-00019
|View full text |Cite
|
Sign up to set email alerts
|

Altered lymphocyte heat shock protein 70 expression in patients with HIV disease

Abstract: Heat shock protein (HSP) expression in lymphocytes isolated from 20 patients with HIV disease and 15 age-matched controls was determined. Fold increases in lymphocyte hsp70 expression after heat shock were 4.52 +/- 2.97 in HIV-positive individuals compared with 2.60 +/- 1.29 for HIV-negative controls (P= 0.001). Given clear roles for HSP in the cross-presentation of antigens, alpha-defensin internalization and pro-inflammatory cytokine production, a further investigation of HSP in HIV patients is merited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 8 publications
0
17
0
Order By: Relevance
“…First, genes encoding cellular chaperones such as the various heat shock proteins. The induction of heat shock proteins has been associated with stress responses including viral infection, and it was shown that recognition of HSP70 by TLR1 activates the innate immune response (41)(42)(43). Of interest was also the induction of X-linked retinitis pigmentosa 2 gene; although the function of this protein has not yet been completely established, it was shown that it may function as a chaperone (44).…”
Section: Discussionmentioning
confidence: 99%
“…First, genes encoding cellular chaperones such as the various heat shock proteins. The induction of heat shock proteins has been associated with stress responses including viral infection, and it was shown that recognition of HSP70 by TLR1 activates the innate immune response (41)(42)(43). Of interest was also the induction of X-linked retinitis pigmentosa 2 gene; although the function of this protein has not yet been completely established, it was shown that it may function as a chaperone (44).…”
Section: Discussionmentioning
confidence: 99%
“…Although the role of cellular heat shock proteins in HIV infection has been investigated by several groups, little information has been generated about the different Hsp family members except Hsp70. The up-regulation of Hsp70 has been reported in HIV infection along with its presence in the virion (23,24), however, its role in HIV-1 infection remains to be established. Hsp70 has been shown to interact with the Vpr protein and inhibit Vpr-induced apoptosis (48).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies reported increased expression of Hsp70 in HIV-1 infection and showed its presence in the virion (23,24,45). Therefore, we assessed the Hsp40 expression level in HIV-1-infected CEM-GFP cells by immunoblotting for Hsp40.…”
Section: Nl4-3 Nef Also Interacts With Hsp40 Both In Vitro and In Vivo-mentioning
confidence: 99%
See 1 more Smart Citation
“…Among a large, nonrandom selection of host proteins, HSP70 was found in the virion membrane of HIV-1; the amount was similar to that of Pol protein, and HSP70 functions as a chaperone during intracellular transport (17). HSP70 mRNA is upregulated in CD4 ϩ T cells infected with HIV-1 (35), and the expression of HSP70 is significantly increased in lymphocytes from HIV-1-infected subjects (1). HSP70 elicits innate immune responses by generating chemokines and cytokines (23,27,38), which exert robust adjuvanticity in nonhuman primates (5).…”
mentioning
confidence: 99%